Challenges in mechanics of time-dependent materials. proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics /: proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics. Volume 2 : (2019) - Unknown
No abstract available